2016
DOI: 10.1152/ajpregu.00297.2015
|View full text |Cite
|
Sign up to set email alerts
|

LA and ALA prevent glucose intolerance in obese male rats without reducing reactive lipid content, but cause tissue-specific changes in fatty acid composition

Abstract: While the cause of Type 2 diabetes remains poorly defined, the accumulation of reactive lipids within white adipose tissue, skeletal muscle, and liver have been repeatedly implicated as underlying mechanisms. The ability of polyunsaturated fatty acids (PUFAs) to prevent the development of insulin resistance has gained considerable interest in recent years; however, the mechanisms-of-action remain poorly described. Therefore, we determined the efficacy of diets supplemented with either linoleic acid (LA) or α-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 46 publications
5
27
2
1
Order By: Relevance
“…In accordance with previous findings (Matravadia et al . ), all animals being supplemented with ALA had significantly decreased levels of n ‐6 fatty acids (LA and AA) and significantly increased levels of n ‐3 fatty acids (ALA, EPA and DHA) in total FFA (Fig. A ), thus validating the effectiveness of our dietary intervention.…”
Section: Resultssupporting
confidence: 64%
“…In accordance with previous findings (Matravadia et al . ), all animals being supplemented with ALA had significantly decreased levels of n ‐6 fatty acids (LA and AA) and significantly increased levels of n ‐3 fatty acids (ALA, EPA and DHA) in total FFA (Fig. A ), thus validating the effectiveness of our dietary intervention.…”
Section: Resultssupporting
confidence: 64%
“…It seems that the essential fatty acids LA and ALA could not ameliorate obesity development and inflammation, and even induce IR in mice . For the treatment of obesity already established, nonetheless, both ALA and LA could rescue impaired glucose homeostasis in obese male rats with no changes in reactive lipid content . Current study reported that ALA and LA sex‐dependently reversed obesity‐induced IR in DIO male and female mice, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Chronic consumption of a high-ALA diet in mice fed a high-fat diet was associated with reduced hepatic glucose production, in association with lower levels of steatosis (30). Also, oral and intravenous glucose tolerance were modestly improved in Zucker diabetic fatty rats fed a high-ALA diet for 8 weeks, although this was not associated with altered expression of any of the hepatic inflammatory markers examined (31). The acute effect of changes in hepatic ALA have not, to our knowledge, been examined.…”
Section: Discussionmentioning
confidence: 98%